Respuesta :

Answer:

t = 5

Step-by-step explanation:

It's asking what t needs to equal for the equation to be equivalent to -44.

-10t + 6 = -44

-10t = -50

t = 5

check

-10(5) + 6 = -44

-50 + 6 = -44

-44 = -44

Answer:

t = 5

Step-by-step explanation:

h(t) = -10t + 6

After that you just write -10t + 6 = -44

Subtract 6 from -44

-44 - 6 = -50

So you will have

-10t = -50

Then you do -10t/-10 = -50/-10

-10t/-10 = t

-50/-10 = 5

So the final answer is t = 5

For proof, plug 5 in.

-10(5) + 6 = ?

-10(5) = -50

-50 + 6 = -44

SO THIS IS THE CORRECT ANSWER LEZZGO!